Evaluation of the Difficulty of Self-Efficacy Items in Mathematics Learning Using Rasch Model Analysis - Faradillah, Ayu; Lutfiyana, Riza Dwi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Singaperbangsa, 2025)
Self-efficacy in learning mathematics is very important because it can help in completing tasks well. The objectives of this study were (1) evaluate the level of difficulty of items in the self-efficacy instrument used in mathematics learning; (2) identify items that were too easy or too difficult; (3) identify items that did not fit the Rasch model; and (4) provide recommendations for improving or developing a more accurate instrument. This study employed a quantitative method with a survey approach. Data were collected from 863 respondents using a self-efficacy questionnaire that was adapted and tested for validity and reliability using the Rasch model. Demographic analysis shows that senior students more often experience low self-efficacy (19,5%). Age also plays a role, with the 19–28 age group having stronger self-efficacy. Gender differences were also observed, with men generally having better self-efficacy than women. In conclusion, demographic characteristics influence students' self-efficacy levels. The implications of this study are the importance of tailored approaches based on educational level, age, and gender in efforts to improve students' self-efficacy in mathematics.